Info Survey Group / Muhammad Aiman Irfan Azhar - Azhar, Muhammad Aiman Irfan (Faculty of Business and Management, 2023)
Info Survey Group, founded in 1998 by the respected Mr. Peter Chaw, brings together the sharpest and sawiest marketing specialists to aid organizations that grasp the basic value of client demands. Over the past 15 years, he has also led numerous customized marketing research projects for large organizations such as Citibank and Maxis. The nature of the service provided is collecting and analysis the data to help other company establish their perfect solution. The industrial training reflect in learn how to know what is the right question to give while doing the survey and many things and the right method that can be use for the question. Survey Monkey can make the work for design questionnaire easily and many functions can be use compared with the google forms method. The swot analysis that can be idenfied is the company have high of the teamwork of communication while have been distributed with high security of information for example provide the CCTV all around the office. The company having problem like lack of the manpower that can burden the employer to do the task and have limited power supply that cause power down sometimes. The company have potential to be a well-known company in the future while build long term relationship with client because of the high performance to fulfill the client needs. The scammer era and competitor technology have been a threats for the company because it will difficult the collecting data process and give possibility for the company to loss the future project. The strategy that can be recommend is the company can build the client trust by improving the security system with modern technology. Other than that, the company can use the high security information as unique selling proposition to attract the client. The company also can take the proactive measure to counter the scammer such as implementing robust data privacy